Investigative journalism in the Sodalicio case - Celis Arévalo, Mariana (2021)
This research work seeks to know and analyze the characteristics of the research reports published as part of the Sodalicio case in the newspaper La República. For this, four variables of analysis have been taken into consideration: general criteria (referring to the headline and introductory text), elements and characteristics of investigative journalism, narrative construction and aspects related to the Christian Life Sodality. Based on this, it is proposed as a methodology to first analyze the reports individually and then land them in a general analysis of the coverage. The conclusion presented determines that the reports of the Sodalicio case respond to a journalistic investigation where it is possible to identify different elements of this discipline, as well as the use of a discursive line that corresponds to literary journalism. Finally, testimonies and data are presented that denounce abuses within the institution.